SYSTEMATIC LITERATURE REVIEW: THE EFFECT OF TOTAL REWARD SYSTEM ON EMPLOYEE JOB SATISFACTION AND PERFORMANCE - Kevin Ghulaman Silmi; Sopiah; Arief Noviarakhman Zagladi (CV. Radja Publika, 2026)
This study systematically reviews 64 articles exploring the impact of total reward systems on job satisfaction and employee performance. Utilizing a Systematic Literature Review (SLR) approach based on the PRISMA methodology, the research examines the effectiveness of both financial and non-financial compensation in enhancing productivity and motivation. Articles were sourced from prominent scientific databases using keywords such as